2020
DOI: 10.19177/jrd.v8e5202051-54
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Strength of Veneer Contact Lens

Abstract: The no prep technique to ceramic veneer have some advantages, one of the most important is the preservation of tooth structure. Purpose: Evaluate fracture resistance in bovine teeth, of ceramic veneer in different thickness (0,3 to 1,0mm). Methods: 60 teeth were selected for this study. Forty fifth ceramic veneer were made for each tooth, variating the thickness in: G1 -0,7mm; G2 -0,5mm; G3 -0,3mm and G4 -1,0mm (control group).Flexural strength test was carried out after 24h of luting. The results were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…While other studies found that reducing thickness exhibited superior fracture strength or no significant difference and it was proposed that the monoclinic phase/tetragonal phase distribution in the Y‐TZP could have influenced the outcome or they explained that by the difference in the methodology or one possible explanation for thinner Y‐TZP ceramics, resulting in higher strength could be the phase transformation t‐m created on the surface because of the machining process and a proportionally thicker monoclinic layer may be created on thinner specimens than on thicker specimens so Since the monoclinic layer has; 3%–4% volume expansion compared to the tetragonal phase, the compressive layer formed at the surface by this layer could have resulted in stronger thinner specimens (Akesson et al, 2009 ; Baptista da Silva et al, 2020 ; Sundh & Sjögren, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While other studies found that reducing thickness exhibited superior fracture strength or no significant difference and it was proposed that the monoclinic phase/tetragonal phase distribution in the Y‐TZP could have influenced the outcome or they explained that by the difference in the methodology or one possible explanation for thinner Y‐TZP ceramics, resulting in higher strength could be the phase transformation t‐m created on the surface because of the machining process and a proportionally thicker monoclinic layer may be created on thinner specimens than on thicker specimens so Since the monoclinic layer has; 3%–4% volume expansion compared to the tetragonal phase, the compressive layer formed at the surface by this layer could have resulted in stronger thinner specimens (Akesson et al, 2009 ; Baptista da Silva et al, 2020 ; Sundh & Sjögren, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 1 Descriptive statistics for different types of ceramics materials and their effect on fracture resistance. tetragonal phase, the compressive layer formed at the surface by this layer could have resulted in stronger thinner (Akesson et al, 2009;Baptista da Silva et al, 2020;Sundh & Sjögren, 2004).…”
Section: The Effect Of Two Thicknesses On Fracture Resistance Of Lami...mentioning
confidence: 99%